Hubungan antara kesiapan menopause dengan kecemasan menghadapi menopause pada ibu Pkk di desa gentan kecamatan bendosari Kabupaten sukoharjo - Nurpatminingsih, Susanti; , H.M. Abi Muhlisin, SKM.,M.Kep (2016)
Menopause was an important time for women. The changes that occur both physically, psychologically and sexually will lead to women facing menopause worried and anxious. Anxiety that they experience was often linked to concerns in the face of a situation that had never occurred before. Women like thwas are usually very sensitive to the emotional impact. The women generally lack the correct information there was only the negative effects that will be experienced after menopause. Thwas study aims to determine the relationship between the readiness of menopause to menopause anxiety faced Mom On Gentan Village, District Bendosari, Sukoharjo. Thwas research was a descriptive study of correlation and cross-sectional design. Sample of research was women aged 40-50 years who will enter menopause in the Village Gentan, District Bendosari, Sukoharjo that as many as 54 respondent's with simple random sampling technique. Collecting data using questionnaires were analyzed using chi square test. The results were obtained c2obs 15.832 (p-value = 0.000), thus H0 was rejected. Conclusion of the study are (1) the readiness of menopause are mostly prepared, (2) concerns facing menopause mostly mild anxiety, (3) There was a relationship Readiness pre-menopausal women with anxiety facing menopause on the PKK in the village Gentan, District Bendosari, Sukoharjo.